A didactic strategy to improve english speaking skills of the tour guides at Valdivia Aquarium, province of Santa Elena, 2015. - Orrala González, Lizeth Paola (2016)
This research paper was done with the objective to improve the English speaking skills through the implementation of a didactic strategy Cooperative Learning at the Valdivia Aquarium to tour guides from that touristic place. This strategy allowed practicing communicative activities in small groups added with the use of didactic materials during the workshops. This research involved the application of surveys and interviews to the administrator, tour guides, foreign tourists and two specialists in the tourism field. Moreover, a diagnostic test and a final test were placed in order to know the speaking level of the tour guides; during the implementation of the proposal, different activities were applied to improve grammar, vocabulary, pronunciation, fluency and interaction to develop oral communication. Consequently, it is recommended that tour guides get a manual as support of their English language.